Study on absorption of ammonia nitrogen by modified bamboo-carbon - ZHOU Shan; CHEN Bin; WANG Jia-ying; YU Jing-quan (浙江大学学报. 农业与生命科学版)
Bamboo-carbon was modified by nitric acid to enhance its absorption capacity. The effects of various parameters such as absorbent dosage, absorption time, absorption temperature and pH on ammonia nitrogen absorption efficiency of bamboo-carbon were investigated, meanwhile the absorption mechanism of ammonia nitrogen by modified bamboo-carbon was studied. The results showed that the ammonia nitrogen absorption capacity of bamboo-carbon was affected by both chemical and structural properties of the bamboo-carbon surface. Compared with bamboo-carbon, the surface properties of modified bamboo-carbon such as oxygen-containing functional groups, specific surface areas, total pore volume were higher, ammonia nitrogen removal ratio was increased from 20.1% to 82.2%, absorption equilibrium time decreased from 6 h to 4 h. Absorption of ammonia nitrogen by bamboo-carbon could be described by Freundlich equation. Furthermore, the absorption performance of modified bamboo-carbon was obviously affected by such parameters as absorbent dosage, absorption time, absorption temperature and pH.